Numerical Construction of Deformation Field Under Wedge Indentation - Syafikah, Ayob; Nor Alisa, Mohd Damanhuri (Universiti Putra Malaysia, 2020)
This research paper presented the construction of the stress distribution in the deformation region under a smooth rigid wedge indenter. The stress components were assumed to satisfy the Mohr-Coulomb yield condition under the plane strain condition. The governing equation for the model was the first order partial differential equation, the stress equilibrium equations. The deformation region was made up of the union of the adjacent elementary boundary value problem and was solved numerically. The region was constructed using Matlab and shows the lip formation on the stress-free surface. The result then compared to analytical solutions. This method is of great interest as it will bring about an increase in efficiency and hence, improvement in industrial productivity. The method is also an alternative for the solution of deformation problems as it is simple and more reliable. This method will consequently improve in designing and developing tools in the related industries and will eventually increase its efficiency